1993
DOI: 10.1007/bf03192236
|View full text |Cite
|
Sign up to set email alerts
|

Moniliformin In wheat and triticale grain

Abstract: Fusarium avanacoum infected wheat and triticale heads in Poland in each season between 1985 and 1989. The average number of heads infected byF avonacaum was 26 % for wheat and 46 % for triticale out of all examined heads withFusarium head blight symptoms.Fusarium-damaged wheat grain, naturally infected byF avenaceum, contained an average of 15.9±7.7 mg moniliformin/kg, healthy looking kernels from the same heads an average of 0.42±0.19 mg moniliformin/kg. Fusarfum-damaged kernels of triticale contained an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 8 publications
1
13
1
Order By: Relevance
“…In addition, mycotoxins tend to be in certain parts of the kernel, which results in varying concentrations in different fractions from processes such as milling (Katta et al 1997). In general, the MON content of the corn in this study was similar to concentrations found in other surveys of food-grade corn in the United States, Canada, and Europe (Scott and Lawrence 1987;Lew et al 1993;MAFF-UK 1998;Gutema et al 2000).…”
Section: Kernel Infection and Mon Contentsupporting
confidence: 80%
“…In addition, mycotoxins tend to be in certain parts of the kernel, which results in varying concentrations in different fractions from processes such as milling (Katta et al 1997). In general, the MON content of the corn in this study was similar to concentrations found in other surveys of food-grade corn in the United States, Canada, and Europe (Scott and Lawrence 1987;Lew et al 1993;MAFF-UK 1998;Gutema et al 2000).…”
Section: Kernel Infection and Mon Contentsupporting
confidence: 80%
“…contamination of other cereals tested may indicate genetic sensitivity to Fusaria. This view is partly supported by the ® ndings that triticale showed 20 % greater sensitivity to Fusarium head blight symptoms than wheat grown in the same period (1985± 1989) in Poland (Lew et al 1993).…”
Section: T Riticalementioning
confidence: 85%
“…To assess the occurrence of MON in cereals on a widespread scale, rapid, reliable, low-cost and sensitive methods of analysis are important. Most analytical methods for the determination of MON use C18 (Scott and Lawrence 1987), extrelut Õ (Lew et al 1993), or a combination of reverse phase and SAX material (Sharman et al 1991) to purify the sample extract followed or preceded by ion pair formation of the toxin. Recently, this method for MON in maize and wheat has been optimized using a clean-up with SAX column and subsequent PR-ion pair-HPLC separation and UV detection (Parich et al 2003) and employed for surveys of MON in Norwegian grain (Uhlig et al 2003).…”
Section: Activities In Mycotoxin Researchmentioning
confidence: 99%